Ab Initio study of the structural, electronic, magnetic, and hyperfine properties of GaxFe4 xN (0.00 e x e 1.00) nitrides - Gil Rebaza, Arles Victor (2013)
The dependence with Ga content (x) of structural, magnetic, and hyperfine properties of GaxFe4–xN compounds has been studied using the full-potential linearized augmented planewave method based on density functional theory. A nonlinear increase of the lattice parameter with x was observed, ascribed to the different metallic radii of Fe and Ga atoms and a magneto-volumetric effect. The magnetic moment per formula unit (Mfu) decreases linearly with x, where the Mfu of GaFe3N is almost half for the corresponding value of γ′-Fe4N, mainly due to the decreasing of magnetic moment of the FeII (3c Wyckoff position) atoms with the number of Ga next nearest neighbors (nnn). The hyperfine parameters of the FeI (1a Wyckoff position) do not change with x, whereas the hyperfine field (Bhf), isomer shift (δ), and quadrupole shift (ε) of the FeII atoms depend linearly with nnn Ga atoms. Furthermore, by use of fixed spin moment calculation to obtain the curve Mfu vs total energy, it was possible to determine that the ground state of GaFe3N belongs to a ferrimagnetic configuration with a lattice parameter similar to the experimental value.